A SYSTEMATIC LITERATURE REVIEW OF THE SERVQUAL MODEL: THEORETICAL DEVELOPMENTS AND RESEARCH TRENDS IN SERVICE QUALITY, SATISFACTION, AND LOYALTY - Yasmin Shafa Mumtaazah; Sambas Ade Kesuma (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the effect of service quality on customer satisfaction and loyalty based on the SERVQUAL model, particularly in the context of higher education and the digital service sector. The study uses a Systematic Literature Review approach based on the PRISMA method with a search of reputable articles in the Scopus database during the period 2023–2025. The identification process included screening titles, abstracts, and theme relevance, followed by an assessment of eligibility based on SERVQUAL dimensions, empirical methods, and the main focus of the research. The data extracted included research objectives, variables, sectors, methods, and key findings. The results of the discussion show that the five dimensions of SERVQUAL, namely tangibility, reliability, responsiveness, assurance, and empathy, have a positive effect on customer satisfaction. In the digital context, additional dimensions such as usability, efficiency, and learnability are increasingly relevant in improving the user experience. The analyzed studies also reveal that satisfaction acts as an important mediator in the relationship between service quality and loyalty, so that service quality not only creates positive perceptions but also encourages the formation of long-term relationships with customers. In the higher education sector, responsiveness and assurance are the main determinants of student satisfaction, while in e-commerce, aspects of trust and convenience strengthen customer loyalty. In conclusion, SERVQUAL remains relevant for measuring service quality across sectors and supports quality management strategies. However, limitations related to the subjectivity of customer perceptions indicate the need for further research through the integration of digital experience variables and switching costs to gain a deeper understanding.